Desarrollo de aplicación móvil académica para motociclistas, como herramienta divulgar el código de tránsito y sus procesos - Ortiz Salazar, Juan Pablo (Corporación Universitaria Minuto de Dios, 2022)
El desconocimiento de las normas básicas de tránsito en los motociclistas son una de las causas accidentalidad en las vías de nuestro país, de acuerdo con las estadísticas del RUN 9.4 millones son motocicletas de 16´042.336 vehículos registrados han sufrido un accidente (Publimotos, 2021), más del 59% de motocicletas a nivel nacional. además del índice más alto en número números comparendos impuestos por las autoridades de tránsito por violación al código de tránsito, mostrando que es necesario generar espacios académicos para que los motociclistas estudien las normas básicas de tránsito.

The lack of knowledge of the basic traffic regulations in motorcyclists is one of the causes of accidents on the roads of our country, according to the statistics of the RUN 9.4 million are motorcycles of 16,042,336 registered vehicles have suffered an accident, more than 59% of motorcycles nationwide. in addition to the highest index in the number of summonses imposed by the traffic authorities for violation of the traffic code, showing that it is necessary to generate academic spaces for motorcyclists to study the basic traffic regulations. Mobile devices have become the preferred massive technological tool for Colombians to access the network, according to the communications regulations commission of the republic (CRC, 2021) "mobile Internet traffic in the second quarter of 2021 reached 430 million GB”, which shows the high flow of network users, for this reason the means of information disclosure are mobile phones. This project seeks to develop an interactive app for motorcyclists with the aim of disseminating the correct application of the traffic code in motorcyclists and monitoring the due process in the adjudication of a subpoena, for the development a software development methodology will be used. and a research methodology that will be described in this document.
Desarrollar una aplicación para dispositivos móviles que permita consultar los procedimientos de tránsito reglamentados en la legislación colombiana para Motociclistas.
Keywords: Desarrollo móvil; APP; Código de transito; Leyes; Motocicletas; Traffic code; mobile app; Traffic violations